Influence of thermal and electrical effects of ohmic heating on C-phycocyanin properties and biocompounds recovery from Spirulina platensis - Santos, Pedro Miguel Ferreira (2020)
Spirulina platensis is interesting for the food industry due to its overall composition and high content in C-phycocyanin. However, the sensitivity of C-phycocyanin makes its extraction a delicate process. The present study focuses on assessing the use of ohmic heating (OH) in the recovery of C-phycocyanin and other relevant compounds as an alternative method to freeze-thawing or conventional heating. Different ohmic and conventional heating treatments were applied both to purified C-phycocyanin and Spirulina powder. Evaluation of fluorescence and circular dichroism showed that moderated electric fields increased C-phycocyanin stability. This was confirmed in the extraction trials which revealed that OH assisted extraction at higher temperatures (44°C), and shorter times (30min) allowed significant higher extraction yield of C-phycocyanin (45 mg/gdw Spirulina), in comparison with conventional heating and freeze-thawing. OH allowed also up to 80% higher yields in phenolic compounds and carbohydrates.